Espectroscopia vibracional (no infravermelho e raman) e espectrofotometria de absorção uv-vis dos óleos de buriti (mauritia flexuosa) e de patauá (oenocarpus bataua) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2012)
In the present work, we characterized Buriti and Pataua oils, fruits from the Obdos city and Lago Grande region. West of Pará. The free fatty acids (FFT) content in the samples was determined by the conventional AOCS titrimetric procedure. The spectroscopic techniques were employed for the characterization of these oils. The techniques used were: Infrared spectroscopy, Raman spectroscopy and absorption spectroscopy in the UV-VIS (200-700 nm). We determined quantitatively the FFT content in the oils by Fourier transform infrared spectroscopy (FTIR). The values obtained by FTIR were compared with values obtained by titration, showing that there is a good correlation between the two results. Thus, we show that it is possible to determine the acid value of these oils with sufficient accuracy for use as food. We also present a detailed investigation of the vibrational spectra of oils and Patauá Buriti using infrared and Raman spectroscopy. Quantum mechanical calculations have been developed to support the experimental results. This allowed us to completely characterize the vibrational spectra of these compounds. The results of Raman spectrum showed clear differences between the species, these differences are in the region entre1157 cm -1 and 1527 cm -1 that appears in the spectrum Buriti but do not appear in the spectrum of Patauá. The absorption spectra indicate the UV-VIS carotenoids in oils Patauá studied, but the kind of carotenoids has not been identified.
Keywords: Plantas oleaginosas; Biotecnologia; Estudos; Óleos vegetais; Óleo de Buriti; Óleo de Patauá; Óbidos; CNPQ::CIÊNCIAS EXATAS E DA TERRA; BIOPROSPECÇÃO E MANEJO DE RECURSOS NATURAIS DA AMAZÔNIA